A Comparative Study of Perceived Social Support and Self-Efficacy among Women with Wanted and Unwanted Pregnancy - Parvin Shahry; Sharareh R. Niakan Kalhori; Azar Esfandiyari; Feresteh Zamani-Alavijeh (Shiraz University of Medical Sciences, 2016)
Background: Unwanted pregnancy induces adverse attitudes regarding pregnancy which is a natural event by increasing mental and socio-economic difficulties. Insufficient maternal care and low adjustment to parental role are known as consequences of unwanted pregnancy. Perceived social support and self-efficacy in pregnancy influence health related behaviors and may play a crucial role in adaptation to pregnancy; this study was conducted to examine and compare the self-efficacy and social support among two groups of women with wanted and unwanted pregnancy. Methods: This analytical descriptive research was conducted on 315 women referred to 13 health centers in the east and west of Ahvaz in 2011. Data were collected via random stratified sampling method through interview. The instrument of this study was a questionnaire in three distinct parts including demographic, modified Persian version of Vaux General social support (Chronbach`s alpha =0.80) and Persian version of self-efficacy scale (Chronbach`s alpha =0.80). Data were analyzed through independent t-test and ANOVA. A P<0.05was considered significant. Results: The mean age of the subjects was 25.8±5.6; unwanted pregnancy occurred in 135 women (42.2%). The mean scores of social support in the two given groups with wanted and unwanted pregnancy were 26.62±4.16 and 22.28±7.57, respectively (P<0.001). Furthermore, the mean scores of self-efficacy for the wanted pregnancy group was 37.77±6.66 and for unwanted pregnancy group it was 31.03±6.31 (P<0.001). Women and their husbands' age, the number of male offspring in family and marriage years were significantly different in the two groups (P<0.05). Conclusion: This study showed that unwanted pregnant women are more likely to be exposed to low level of perceived social support and self-efficacy. Therefore more studies and interventions are recommended to be conducted to analyze the effect of family and friends' supports on unwanted pregnant women's perceived social support and self-efficacy and its adverse consequences.